2006
DOI: 10.1016/j.ejphar.2006.08.062
|View full text |Cite
|
Sign up to set email alerts
|

Long-term angiotensin II AT1 receptor inhibition produces adipose tissue hypotrophy accompanied by increased expression of adiponectin and PPARγ

Abstract: To clarify the mechanism of the effects of angiotensin II AT 1 receptor antagonists on adipose tissue, we treated 8 week-old male Wistar Kyoto rats with the angiotensin II AT 1 receptor antagonist Candesartan cilexetil (10 mg/kg/day) for 18 weeks. Candesartan cilexetil reduced body weight gain, decreased fat tissue mass due to hypotrophy of epididymal and retroperitoneal adipose tissue and decreased adipocyte size without changing the number of adipocytes. Candesartan cilexetil decreased serum leptin levels an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
121
3
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(137 citation statements)
references
References 66 publications
10
121
3
3
Order By: Relevance
“…These effects of AT1 receptor blockade were associated with increased glucose uptake in adipose tissue, reduction in adipocyte size, and increased expression of peroxisome proliferator-activated receptor (PPARγ) in adipose tissue. Interestingly, similar findings were demonstrated in rats administered an AT1 receptor antagonist and fed a normal diet [30]. Further studies are required to define whether these effects of AT1 receptor blockade are present in obese humans, and whether they influence obesity-related hypertension.…”
Section: Effects Of Ang II On Adipocytessupporting
confidence: 54%
“…These effects of AT1 receptor blockade were associated with increased glucose uptake in adipose tissue, reduction in adipocyte size, and increased expression of peroxisome proliferator-activated receptor (PPARγ) in adipose tissue. Interestingly, similar findings were demonstrated in rats administered an AT1 receptor antagonist and fed a normal diet [30]. Further studies are required to define whether these effects of AT1 receptor blockade are present in obese humans, and whether they influence obesity-related hypertension.…”
Section: Effects Of Ang II On Adipocytessupporting
confidence: 54%
“…The presence of this receptor has been reported recently in human subcutaneous (Engeli et al 2005, Achard et al 2007) and visceral adipose tissue (Zorad et al 2006, Achard et al 2007). In our study, expression of the (pro)renin receptor could be detected in both white and brown PVATs, with higher levels of mRNA expression in periaortic fat.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study on body weight gain are consistent with recent reports in rats treated with angiotensin AT 1 per day) also reduced epididymal fat mass. 19,21 Food intake was reduced in both these studies, which could have accounted for the lower body weight and fat mass ( Table 1). The investigators also measured increases in other mechanisms of reducing fat mass, showing that AT 1 receptor inhibition increased whole body energy utilization 21 and the plasma concentration of the adipocytokine, adiponectin, which enhances fatty acid metabolism.…”
Section: Mechanisms Underlying the Reduction In Fat Massmentioning
confidence: 99%
“…In general, studies in rats showed that blockade of the RAS with an AT 1 receptor antagonist reduces body weight gain and visceral or epididymal fat mass. [19][20][21] This effect is usually accompanied by a reduction in food intake, and some studies also suggest that increases in fatty acid metabolism or energy expenditure might be part of the mechanism. However, some AT 1 receptor antagonists were more effective than others, 21 and this difference was attributed to the additional property of some drugs in this class, which are partial agonists at peroxisome proliferator-activated receptor (PPAR)-g. 22 In humans, trials of AT 1 receptor antagonists with low numbers of subjects did not produced significant weight loss, 18,23 but one study reported a significant reduction in visceral fat.…”
Section: Introductionmentioning
confidence: 99%